Prophylactic use of low-dose interleukin-2 and the clinical outcomes of hematopoietic stem cell transplantation: A randomized study. (1st December 2016) - Zhao, Xiang-Yu; Zhao, Xiao-Su; Wang, Yu-Tong; Chen, Yu-Hong; Xu, Lan-Ping; Zhang, Xiao-Hui; Han, Wei; Chen, Huan; Wang, Yu; Yan, Chen-Hua; Wang, Feng-Rong; Wang, Jing-Zhi; et al.
ABSTRACT: Leukemia relapse and chronic graft-versus-host disease (cGVHD) are still major obstacles of allogeneic hematopoietic stem cell transplantation (allo-HSCT). The numbers and activity of natural killer (NK) and T-regulatory cells can be increased post-transplantation by exposure to interleukin-2 (IL-2). We tested whether administering low-dose IL-2 would decrease leukemia relapse while reducing cGVHD after allotransplantation. This controlled, open-label randomized trial included 90 recipients of allotransplants. Subjects were randomized in a 1:1 ratio to either receive or not receive low-dose IL-2 during the early post-transplantation period. Patients in the IL-2 arm received a subcutaneous injection of low-dose IL-2 (1×10 6 U/d) on day 60 after allo-HSCT. IL-2 was administered daily for 14 d followed by a 14-d hiatus. The primary endpoint was the cumulative incidence of leukemia relapse (CIR). Three-year CIRs for the IL-2 arm and control arm were 23% (range 16–30%) and 11% (range 6–15%; p = 0.20), respectively. Minimal residual disease-positive (MRD+) tests were more common in the IL-2 arm compared to the control arm (36% [range 29–44%] vs. 15% [range 10–20%], p = 0.03). The cumulative incidence of moderate-to-severe chronic GVHD (cGVHD) was lower in the IL-2 arm compared to the control arm (33% [range 26–39%] vs. 57% [range 49–64%), p = 0.02). Therefore, the 3-y GVHD-free and GVHD progression-free survival (GPFS) rates were significantly higher in the IL-2 arm compared to the control arm (47% [range 39–55%] vs. 31% [range 25–38%], p = 0.048). Blood Tregs, NK cells, and NK-cell cytotoxicity were increased in subjects in the IL-2 arm between 3 mo and 6 mo post-transplantation. Administration of low-dose IL-2 during the immediate post-transplantation period was associated with a higher GPFS but did not decrease the CIR.